Mapping Healthcare Professional Regulation Globally With the Structural Quality and Modernization Index - Mohammad E. M. Mahfouz; Jomanah A. Eid; Ahmed S. Abdel‐Moneim (World Medical & Health Policy, 2026)
ABSTRACT The recognition of healthcare professional qualifications across jurisdictions remains uneven, despite frameworks such as the European Union's Directive 2005/36/EC. In this study, we developed and applied the Structural Quality and Modernization Index (SQMI), a novel tool specifically designed for this research to enable comparative benchmarking of modernization across diverse health professional regulatory systems. A systematic policy analysis covering 2005–2025 was conducted across seven jurisdictions, evaluating competency‐based education integration, accreditation structures, licensing mechanisms, continuous professional development, digitalization, Sustainable Development Goal alignment, and regulatory transparency. SQMI scores ranged from 30/100 in the European Union to 83/100 in Canada. Canada, the United States, and the United Kingdom demonstrated consistently strong performance across most domains, whereas the European Union exhibited structural fragmentation and limited supranational coordination. Saudi Arabia showed the most rapid modernization trajectory, improving by 5.8 points per year between 2015 and 2025, driven by digital infrastructure development and alignment with national and global health priorities. Correlation analysis revealed strong relationships between accreditation and standardized licensing ( ρ = 0.96) and between digitalization and SDG alignment ( ρ = 0.91), indicating that modernization domains evolve synergistically. Overall, the findings highlight regulatory modernization as a multidimensional process requiring coordinated progress in competency frameworks, accreditation systems, licensing standards, and digital infrastructure. The SQMI provides an evidence‐informed instrument to support policy reform, identify structural gaps, and promote international benchmarking toward more coherent and future‐ready healthcare professional regulation.